Quality of Payang Boat and Stability - Yopi Novita, Yopi; Neni Martiyani, Neni; Eva Ariyani, Eva (Journal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
A good stability of a fishing vessel determines the safety and the success of fishing operation. One of the critical factors affecting the quality of fishing boatâs stability is the on board loads arrangement. However, it is generally ignored by traditional fishermen, such as fishermen of payang boat. This condition may increase the possibility of capsizing as a result of less stability. A payang fishing boat should have a good stability. It is because while conducting fishing operation, this fishing boat should be capable of quick manoeuvering. This research aimed to analyse the stability of the boat in an existing loads arrangement and determine the arrangement for the better stability.Â  This research was conducted in two phases. The first phase was conducting a survey which to capture existing condition. The second one was developing a simulation of loads arrangement to gain the better parameter of stability. The results showed that the typical loads arrangement applying by traditional fishermen (existing condition) resulted on poor stability. Better stability was produced by placing more cargos under deck and avoiding overload on the deck.